The lifeguards : a novel / Amanda Eyre Ward. - Ward, Amanda Eyre, 1972- (Ballantine Books, 2022)
"The bonds between three picture-perfect, viciously protective mothers are tested when their sons uncover a horrible crime in this provocative novel from the New York Times bestselling author of The Jetsetters. In Austin's Zilker Park, vigilance and money are enough to keep one insulated from the world's problems and inconveniences. Here, three mothers-Whitney, Annette, and Liza-have grown thick as thieves, and so have their fifteen-year-old sons. While each of them has their own set of values and backgrounds, they share the belief that they can shelter their boys from an increasingly dangerous world. They've raised their families together, and their three sons are about to begin a carefree summer as lifeguards. Their friendship is unbreakable--as safe as the neighborhood where they've raised their sweet little boys. Until the body is found. One night, the three women have been chatting away, drinking wine, when their boys come back with a harrowing story about finding a young woman dead beside a swimming hole in the Greenbelt, a swath of hiking trails and dim wilderness areas that runs through their neighborhood. They swear they haven't done anything. They agree not to call the police-because who would want to cause a scene, to topple their fragile images and arouse suspicion? What choice do mothers have but to believe their sons? All families harbor secrets. Privately, none of them is sure that the boys are telling the truth. And with each woman questioning her son-and her friends' sons-each wonders how many lies they've told each other. The Lifeguards is a riveting, high-stakes novel about the secrets we tell to protect the ones we love-and how sometimes your closest neighbor and ally can become your most dangerous foe"-- Provided by publisher.
Keywords: Mothers and sons -- Fiction.; Friendship -- Fiction.; Mother-son relationship -- Fiction.; Suspense fiction.